Digital dermatitis: treatment and control. Issue 2 (21st May 2013) - Bell, Nick J; Blowey, Roger; Laven, Richard; Reader, Jon; Smith, Rob
<x xml:space="preserve">Abstract</x> Bovine digital dermatitis has been an increasingly important cause of lameness over the last 25 years. Research would suggest the treatment and control is relatively simple although antibacterial licensing laws make choices for practitioners less straightforward. Furthermore, the appearance of 'non‐healing' claw lesions has created a new challenge for treatment and control. For optimal prevention attention to foot hygiene, biosecurity and breeding is needed but these are more challenging for farmers to implement than daily foot disinfection protocols.